The subtle art of not giving a fuck a counterintuitive approach to living a good life - Manson, Mark. (New York HarperOne, 2016)
In this generation-defining self-help guide, a superstar blogger cuts through the crap to show us how to stop trying to be positive all the time so that we can truly become better, happier people.
Keywords: Conduct of life